Stochastic Modeling for Analyzing Scalability Impact of Lottery Scheduling using Proportion Reformation (International Journal of Engineering and Computer Science, 2016)
For effective processor scheduling, algorithms are required to develop not only for fair scheduling but also for efficient implementation of resource management with rapid adjustment to control over relative execution rates. Proportional share scheduler assure that each job obtain a certain percentage of processor time. Lottery scheduling is based on randomized approach to achieve proportional share resource management where resources are allocated to the clients in proportion to their respective weights. In this paper conventional lottery scheduling scheme is designed and extended along with some conditions to get new scheduling schemes. Stochastic modeling is applied for study and analysis.